Advancements and Challenges in Addressing Zoonotic Viral Infections with Epidemic and Pandemic Threats - Munazza Fatima; Timothy An; Pil-Gu Park; Kee-Jong Hong (Viruses)
Zoonotic viruses have significant pandemic potential, as evidenced by the coronavirus pandemic, which underscores that zoonotic infections have historically caused numerous outbreaks and millions of deaths over centuries. Zoonotic viruses induce numerous types of illnesses in their natural hosts. These viruses are transmitted to humans via biological vectors, direct contact with infected animals or their bites, and aerosols. Zoonotic viruses continuously evolve and adapt to human hosts, resulting in devastating consequences. It is very important to understand pathogenesis pathways associated with zoonotic viral infections across various hosts and develop countermeasure strategies accordingly. In this review, we briefly discuss advancements in diagnostics and therapeutics for zoonotic viral infections. It provides insight into recent outbreaks, viral dynamics, licensed vaccines, as well as vaccine candidates progressing to clinical investigations. Despite advancements, challenges persist in combating zoonotic viruses due to immune evasion, unpredicted outbreaks, and the complexity of the immune responses. Most of these viruses lack effective treatments and vaccines, relying entirely on supportive care and preventive measures. Exposure to animal reservoirs, limited vaccine access, and insufficient coverage further pose challenges to preventive efforts. This review highlights the critical need for ongoing interdisciplinary research and collaboration to strengthen preparedness and response strategies against emerging infectious threats.